How relevant are district characteristics in explaining subjective health in Germany? - A multilevel analysis - Schneider, Sven; Diehl, Katharina (Social Science & Medicine, 2011)
This study was the first multilevel analysis to investigate the possible impact of macro-level factors on individual self-rated health over and above individual characteristics across Germany. This is especially interesting against the background of German history and the persistent disparity between Eastern and Western Germany. In this paper, the 439 German administrative districts, called Landkreise, provided the macro-level characteristics for this study. Altogether, 5516 individuals in 437 districts were included from data collected between 2005 and 2007.Our results show a significant association between the district unemployment rate and subjective health. The impact remains significant after adjusting for individual variables, including individual employment status. Furthermore, a significant association was found between subjective health and the degree of rurality, the proportion of elderly inhabitants and the proportion of foreigners. However, the variance of these was zero. In conclusion, our findings indicate an independent association between the unemployment rate of districts and individual self-rated health. Area mechanisms identified for other countries seem to exist in Germany, too, beyond the well-known differences between the Federal Republic of Germany and the German Democratic Republic that still influences individual health outcomes. © 2011 Elsevier Ltd.
CRIS-Team Scopus Importer:2021-12-06
Keywords: Areas; Germany; Health status; Regional unemployment; Self-rated health; Subjective health